Influence of diglyme and cumene additives upon emission and combustion behaviour of diverse biodiesel fuelled diesel engine - Swarup Kumar Nayak; Dinesh Babu Munuswamy; Ganesan Subbiah; Mallireddy Naresh; Yuvarajan Devarajan (Results in Engineering)
The growing need for sustainable and eco-friendly fuels aligns with global efforts to achieve the United Nations Sustainable Development Goals (SDGs), particularly SDG 7 (Affordable and Clean Energy), SDG 13 (Climate Action), and SDG 12 (Responsible Consumption and Production). This study addresses these goals by investigating the potential of biodiesel blends supplemented with innovative fuel additives to improve engine performance and reduce environmental impact. Specifically, the effects of diglyme (DG) and cumene (CU) as fuel additives on the combustion, performance, and emission characteristics of diesel engines fueled with jojoba methyl ester (JME), polanga oil methyl ester (PME), and their blended variant mixed methyl ester (MME) were evaluated. Experiments were conducted on a single-cylinder, 4-stroke, water-cooled, direct injection diesel engine operating at a constant speed of 1500 rpm and injection timing of 21ºbTDC under varying load conditions (0–5.02 kW). DG (5 % vol./vol.) was used as a cetane improver, while CU (5 % vol./vol.) functioned as an antioxidant. The results demonstrated that the blends MME15+CU5 and MME15+DG5 exhibited superior thermo-chemical properties and engine performance. MME15+CU5 achieved an 8.77 % increase in brake thermal efficiency (BTE), along with reductions in brake-specific energy consumption (BSEC) (5.64 %) and exhaust gas temperature (EGT) (12.02 %) at peak load. Similarly, MME15+DG5 delivered a 15.78 % improvement in BTE, with reductions in BSEC (17.11 %) and EGT (5.48 %). Emission analysis revealed significant reductions in CO (53.52 %), HC (81.25 %), NOx (26.11 %), and smoke opacity (25.79 %) for MME15+DG5 compared to diesel. These findings underscore the potential of (diglyme and cumene) additives enhanced biodiesel blends as sustainable, efficient alternatives to conventional diesel, contributing to the reduction of greenhouse gas emissions (SDG 13) and fostering responsible energy production and consumption (SDG 12), while promoting access to clean energy solutions (SDG 7).